2022
DOI: 10.3389/feduc.2022.867447
|View full text |Cite
|
Sign up to set email alerts
|

Content and Language Integrated Learning Implementation Through Team Teaching in Biology Lessons: A Quasi-Experimental Design With University Students

Abstract: Can engaging university students in Content and Language Integrated Learning (CLIL) increase their achievement in Biology and English language? The current study explored the effectiveness of team teaching enhanced CLIL on student achievement. Framed in interdisciplinary/cross-curricular teaching, we examined the effect of CLIL strategy on student achievement in a quasi-experimental study with a sample of Biology education students (N = 25) assigned to control and experimental groups. The topic taught through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
1
8
0
4
Order By: Relevance
“…The issue of TSs has gained noticeable attention over the last years because nobody can gain independence in learning if they lack these essential skills ( Stal and Paliwoda-Pękosz, 2019 ; Vadivel et al, 2021 ; Satayev et al, 2022 ). Previously, different terms such as basic skills, key competencies, employability skills, the 21 st -century skills, and transversal competencies have been used interchangeably for TSs (Viska project, 2017; Ghadermarzi and Mohamadi, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of TSs has gained noticeable attention over the last years because nobody can gain independence in learning if they lack these essential skills ( Stal and Paliwoda-Pękosz, 2019 ; Vadivel et al, 2021 ; Satayev et al, 2022 ). Previously, different terms such as basic skills, key competencies, employability skills, the 21 st -century skills, and transversal competencies have been used interchangeably for TSs (Viska project, 2017; Ghadermarzi and Mohamadi, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main explanation is that teachers do not receive sufficient CLIL principles and methodology training. Satayev et al (2022) recently studied if engaging university students in CLIL can increase their achievement in biology and English language. In a quasiexperimental study with a sample of 25 students from Almaty, they found that CLIL effectively taught content and language for science subjects.…”
Section: English-medium Education In Kazakhstanmentioning
confidence: 99%
“…Such environments are often created through inquiry learning, which combines hands-on activities with experiments and the exploration of a scientific phenomenon (Hampton and Rodriguez, 2001;Campillo-Ferrer and Miralles-Martínez, 2022;Roth et al, 2022). Thereby, students engage in meaningful scientific practice, such as describing observed phenomena, formulating hypotheses, assessing results, and reflecting on findings, which demands the use of a discipline-specific register (Stoddart et al, 2002;Satayev et al, 2022). To foster such practice in science classrooms, Tolbert et al (2019) suggested four dimensions of instruction, including contextualization, scientific reasoning, scientific discourse and scientific literacy.…”
Section: Theoretical Background Content and Language Integrated Learningmentioning
confidence: 99%
“…To foster such practice in science classrooms, Tolbert et al (2019) suggested four dimensions of instruction, including contextualization, scientific reasoning, scientific discourse and scientific literacy. This way, language is inherently contextualized-no longer a mere catalyst-and helps students to structure and communicate acquired information (Lemke, 1990;Hampton and Rodriguez, 2001;Satayev et al, 2022). A study by Piacentini et al (2022) showed that in addition to science and language learning rewards for students, CLIL also benefitted teachers to recognize pattern among their students that they have been oblivious to previously.…”
Section: Theoretical Background Content and Language Integrated Learningmentioning
confidence: 99%
See 1 more Smart Citation